PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP TAX AVOIDANCE - Ayu Citra Maharani; Muhammad Yusuf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the effect of Corporate Governance and Profitabilty on Tax Avoidance in manufacturing companies in consumer goods industry sector that listed in Indonesia Stock Exchange. Proxy of Corporate Governance consist of Independent commissioners, Mangerial Ownership, Audit Comittee, and Quality Audit whereas Profitability used Return on Assets as proxied. Population in this study are manufacturing companies in consumer goods industry sector that listed in Indonesia Stock Exchange period 2015-2019 there are 53 companies. Purposive sampling used to sampel taking method and 23 was obtained. Multiple linear regression analysis is used for hypothesis testing. Based on the result data testing shows that Independent Comissioner have a positive and significant effect on Tax Avoidance. Return on Assets have a negative and significant effect on Tax Avoidance. Meanwhile, Managerial Ownership, Audit Committee, and Quality Audit have no signifficant effect on Tax Avoidance. Keywords: Tax Avoidance, Corporate Governance, Profitabilty